Steve Jobs : the man who thought different : a biography - Blumenthal, Karen (New York : Bloomsbury, 2012)
Traces the inspiring life and career of the late founder of Apple, covering topics ranging from his struggles as an adopted child and a college dropout to his Buddhist faith and friendship with Steve Wozniak, in a portrait framed around his inspirational Stanford University commencement speech.
Includes bibliographical references (p. [278]-283) and index.
Keywords: Jobs, Steve, -- 1955-2011 -- Juvenile literature; Apple Computer, Inc. -- History -- Juvenile literature; Computer engineers -- United States -- Biography -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Businesspeople -- United States -- Biography -- Juvenile literature; Computer industry -- United States -- History -- Juvenile literature